Internalisasi Karakter Religius pada Siswa melalui Program Praktikum Ibadah dan Zikir - Sinaga, Rizky Awaliyah; Mahariah, Mahariah (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
The worship and remembrance practicum program is meant to help students to internalize religious values. This study was conducted at MIS Al-Washliyah Insanul Kamil located in Melati Kebun, Pegajahan District, Serdang Bedagai Regency; by using qualitative methods and a phenomenological approach. The sources of data in this study consisted of school principals, teachers of worship and remembrance practicum programs, and students. Data were collected through observation, interviews, and documentation analysis. The purpose of this study focused on background, strategies for internalizing religious character in students, as well as inhibiting and supporting factors in the prayer and remembrance practicum program. The findings of the analysis showed that the background of the program is based on the awareness of the importance of providing in-depth guidance regarding worship and remembrance toward students in daily life to create perfect people. The internalization strategy is carried out through the program and interspersed with advice regarding the primacy of the material being taught. Supporting factors in the program include students who are guided by competent teachers, while the inhibiting factor is the lack of supporting tools that have not been fulfilled such as the torso.